ANALISIS NILAI TINGKAT KERUSAKAN PERMUKAAN JALANPEKERASAN LENTUR MENGGUNAKAN METODE IRI(INTERNATIONAL ROUGHNESS INDEX) DAN PAVEMENT CONDITIONINDEX (PCI)(STUDI KASUS: JALAN SULTAN SYARIF KASIM KEC. SUNGAI APIT KABUPATEN SIAK) - HAIKAL, M. (P3M Politeknik Negeri Bengkalis, 2025)
This research aims to analyze the level of damage to the flexible pavement surface on Jalan Sultan Syarif Kasim, using the IRI and PCI methods and applying GIS. The IRI method is used to measure road surface unevenness, while PCI is used to assess the structural and functional condition of roads based on the type and severity of damage. Data obtained from surveys was analyzed using GIS software, namely ArcGis, to map the distribution of road damage and identify road segments that require priority repairs. From the data processing, the results obtained were 25% perfect condition, 5% very good condition, 0% good condition, 5% fair condition, 50% bad condition, and 15% very bad condition according to the PCI method, while the damage assessment results used the IRI method assisted by The Roadroid application shows that Jalan Sultan Syarif Kasim is 100% heavily damaged. These two results draw the same conclusion that Jalan Sultan Syarif Kasim needs maintenance in the form of road improvements. The damage data is then integrated into ArcGis to produce a damage distribution map containing 65 damage points along 1 km.